Studies on complexes of Co(II), Ni(II), Cu(II), and Cd(II) with acetophenone and 4-hydroxyacetophenone 4-aminobenzoylhydrazones - Singh B.; Narang K.K.; Srivastava R. (My University, 2025)
Metal(II) complexes of the types [M(L)Cl2(H2O)] and [M(L′)2Cl2] [M = Co(II), Ni(II), Cu(II) and Cd(II), L = acetophenone- 4-aminobenzoylhydrazone (APABH), NH2C6H4CONHN=C(CH3)C 6H5 and L′ = 4-hydroxyacetophenone 4-aminobenzoylhydrazone (HAPABH), NH2C6H4CONHN=C(CH3)C 6H4OH were prepared and characterized by elemental and thermal analyses, molar conductance, magnetic susceptibility, infrared, NMR and electronic spectral studies. Some of the complexes were screened against E. coli, and Aspergillus niger for biological activity. The antibacterial activity of hydrazones and their complexes increases with increase of the concentration of solutions. At each concentration copper(II) complexes are more active than the Zinc(II) complexes with both hydrazones. The antifungal activity of the complexes is less than their parent ligands.